2020
DOI: 10.1186/s13063-020-4216-4
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct low-dose ketamine infusion vs standard of care in mechanically ventilated critically ill patients at a Tertiary Saudi Hospital (ATTAINMENT Trial): study protocol for a randomized, prospective, pilot, feasibility trial

Abstract: Background: A noticeable interest in ketamine infusion for sedation management has developed among critical care physicians for critically ill patients. The 2018 Pain, Agitation/sedation, Delirium, Immobility, and Sleep disruption guideline suggested low-dose ketamine infusion as an adjunct to opioid therapy to reduce opioid requirements in post-surgical patients in the intensive care unit (ICU). This was, however, rated as conditional due to the very low quality of evidence. Ketamine has favorable characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This was an investigator-initiated, pilot, single-center, parallel-group, open-label RCT (Registered with ClinicalTrials.gov: NCT04075006, current controlled trials: ISRCTN14730035, and Saudi Food and Drug Authority 19063002). The study was approved by King Faisal Specialist Hospital and Research Center (KFSH&RC) Institutional Review Board (IRB) (Riyadh, SA, IRB# 2191187) and full study protocol was published previously [ 23 ]. The trial was conducted according to CONSORT guidelines for pilot and feasibility trials and reported according to pilot study checklist [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an investigator-initiated, pilot, single-center, parallel-group, open-label RCT (Registered with ClinicalTrials.gov: NCT04075006, current controlled trials: ISRCTN14730035, and Saudi Food and Drug Authority 19063002). The study was approved by King Faisal Specialist Hospital and Research Center (KFSH&RC) Institutional Review Board (IRB) (Riyadh, SA, IRB# 2191187) and full study protocol was published previously [ 23 ]. The trial was conducted according to CONSORT guidelines for pilot and feasibility trials and reported according to pilot study checklist [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Successful recruitment was defined as > 3 patients enrolled per month. Protocol adherence was defined as > 75% of protocolized intervention and assessment of protocol deviation and violation [ 23 ]. We conducted educational sessions for clinicians, nurses, and hospital pharmacies to facilitate implementation of protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The ATTAINMENT trial was registered with ClinicalTrials.gov: NCT04075006, current controlled trials: ISRCTN14730035, and Saudi Food and Drug Authority: SCTR #19063002. The full study protocol has been published previously [13] . The study was conducted according to the Consolidated Standards of Reporting Trials (CONSORT) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Data were stored online in REDCap web application and data quality assessments were executed routinely to ensure completion and accuracy. Details about the variables extracted from the electronic medical record were reported previously [13] .…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation